2015
DOI: 10.1177/1082013215572029
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable diets: The interaction between food industry, nutrition, health and the environment

Abstract: Everyday great amounts of food are produced, processed, transported by the food industry and consumed by us and these activities have direct impact on our health and the environment. The current food system has started causing strain on the Earth's natural resources and that is why sustainable food production systems are needed. This review article discusses the need for sustainable diets by exploring the interactions between the food industry, nutrition, health and the environment, which are strongly intercon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(73 citation statements)
references
References 29 publications
1
64
0
8
Order By: Relevance
“…160 Recently, the findings in this advice were confirmed in various peer-reviewed articles. 161, 162, 163, 164 The Committee compared the findings in that advice with those of the current guidelines and concluded that complying to a number of guidelines will not only result in health gain but also in a lower ecological burden. Limiting meat consumption is also desirable from an ecological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…160 Recently, the findings in this advice were confirmed in various peer-reviewed articles. 161, 162, 163, 164 The Committee compared the findings in that advice with those of the current guidelines and concluded that complying to a number of guidelines will not only result in health gain but also in a lower ecological burden. Limiting meat consumption is also desirable from an ecological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary recommendations to eat more fish are (potentially) unsustainable , Horgan et al (2016), Lang (2014), Merrigan et al (2015), Reynolds et al (2014), Riley and Buttriss (2011), Selvey and Carey (2013), Westhoek et al (2011) Consuming seafood presented as a conflict between health and environmental sustainability Alsaffar (2015), , Macdiarmid (2013), Macdiarmid et al (2012), Mitchell (2011), Buttriss (2011), van Dooren et al (2014) Express concern over environmental/biotic impacts of fishing Buttriss and Riley (2013), Carlsson-Kanyama and González (2009), , Garnett (2011, Heller et al (2013), Mitchell (2011), Nijdam et al (2012, Ruini et al (2015), Tukker et al (2011), Tyszler et al (2015 Advocate consumption of sustainable wild-capture seafood Buttriss and Riley (2013), , Macdiarmid (2013), Reynolds et al (2014), Buttriss (2011), Tyszler et al (2015) No scope for increased production/consumption Fazeni andSteinmüller (2011), Jalava et al (2014), Stehfest et al (2009) Use of wild-capture fish for aquafeed should be reduced Reynolds et al (2014), Selvey and Carey (2013), Westhoek et al (2011) Use of crops for aquafeed will increase footprint of seafood Gephart et al (2016), Westhoek et al (2011) T A B L E 2 Themes for seafood identified in the sustainable diets literature | 613…”
Section: Theme Sourcementioning
confidence: 99%
“…The result of limited access to suitable fishery and aquaculture data is that some researchers modelling future sustainable diets are not allowing for any future increase in seafood consumption (Fazeni & Steinmüller, 2011;Jalava et al, 2014;Stehfest et al, 2009), while others refer to seafood only briefly in the context of it being unsustainable (see, e.g., Allen, Prosperi, Cogill, & Flichman, 2014;Alsaffar, 2015;Johnston et al, 2014). However, seafood plays, and will continue to play, an important role in the global food system, with annual per capita consumption projected to increase (World Bank, 2013).…”
Section: Implications Of Inadequate Inclusion Of Seafood In Sustainmentioning
confidence: 99%
“…Think of the toxic waste disposal in the so-called "triangle of death", located the eastern area of the Campania Region in Southern Italy, where massive illegal dumping have been operated by camorra 10 and where the adverse effect on human health in this area have caused a high increase of liver and lung cancer mortality and congenital malformation (Triassi et al 2015). Think of food distribution: on Planet Earth, some people suffer from malnutrition; other people eat processed food, causing problems both to their health and to the environment (Alsaffar 2016); some other people waste gourmet food, which comes in unsustainable containers … 9 Held on September 21, 2014, this is considered the largest climate change march in history, with an estimated number of participants on the order of 400.000. See Feeley 2014. 10 A type of mafia originated in the region of Campania and characterized by illegal activities.…”
Section: Behind the Scenes -Act Imentioning
confidence: 99%